Fostering professional growth in academic librarians: A SoTL-based lens for Research Data Management capacity building - Mohd Ikhwan Ismail,; S.F. Samsuddin,; Abrizah, A. (Malaysian Journal of Library and Information Science, 2024)
This study examines the use of the Scholarship of Teaching and Learning (SoTL) as a framework for capacity building in Research Data Management (RDM) among academic librarians. It explores how SoTL principles are applied through interventions such as librarian-led training sessions to develop RDM skills, while presenting best practices and addressing professional growth challenges. A qualitative approach was used, involving interviews with 15 purposively sampled librarians from research-intensive universities in Malaysia actively engaged in RDM services. Key findings show that librarians develop their expertise through four key approaches: acquiring RDM competency; utilizing professional connections; building research partnerships, and initiating RDM services. Additionally, the study reveals that librarians engage in capacity building through SoTL and peer teaching by actively participating in knowledge-sharing practices, both formally and informally, within and outside their institutions. SoTL proved beneficial in fostering a continuous learning cycle as librarians taught their peers. This study concludes that SoTL can reshape professional development among academic librarians.